A meta-analysis and systematic review of the clinical efficacy and safety of platelet-rich plasma combined with hyaluronic acid (PRP + HA) versus PRP monotherapy for knee osteoarthritis (KOA) - Dan Du; Yuan Liang (Journal of Orthopaedic Surgery and Research)
Abstract Introduction KOA, a chronic degenerative joint disease, is commonly treated with intra-articular HA and PRP, used alone or in combination. However, the efficacy and safety of combination therapy (PRP + HA) remain unclear. Aim The aim of this systematic review and meta-analysis is to assess the clinical effectiveness and safety profile of PRP + HA versus PRP monotherapy for KOA. Material and methods A systematic search was conducted using four electronic databases (PubMed, EMBASE, Scopus, and Cochrane Library) to select publications published in peer-reviewed journals. The mean difference (MD) and risk ratio (RR) was calculated, along with their 95% confidence intervals. We assessed heterogeneity using Cochrane Q and I2statistics and the appropriate p-value. The analysis used RevMan 5.4. GRADE system was used for evidence assessment for each outcome parameter. Results This meta-analysis of 11 RCTs (n = 1023 KOA patients) revealed that PRP + HA has substantial effectiveness than PRP alone in reducing OMAC total scores [MD -1.77 (95% CI -2.20 to − 1.34); I2 = 10%, and p < 0.001], VAS scores [MD -4.27 (95% CI -4.96 to − 3.58); I2 = 13%, and p < 0.001], and Lequesne index score [MD -5.48 (95% CI -6.56 to − 4.40); I2 = 16%, and p < 0.001], while increasing IKDC scores [MD -2.10 (95% CI -3.70 to − 0.50); I2 = 9%, and p = 0.01], with low risk of adverse events [RR 0.41 (95% CI 0.35 to 0.48); I2 = 12%, and p < 0.001]. Conclusion This meta-analysis reveals that, for patients with KOA, PRP + HA therapy is safe and yields better outcomes in pain relief and functional improvement compared to PRP monotherapy.